Effects of gravity and variable thermal properties on nanofluid convective heat transfer using connected and unconnected walls. (1st September 2018) - Li, Qianqian; Wang, Jin; Wang, Jiansheng; Baleta, Jakov; Min, Chunhua; Sundén, Bengt
Highlights: Nusselt number is underestimated by not using variable properties. Increasing nanoparticle volume fraction decreases the average Nusselt number. Reduction of gravity weakens heat transfer due to low buoyancy force. Nusselt number varies along the heated surface as gravity is considered. Heat transfer enhancement of 89.9% is obtained by using unconnected heated walls. Abstract: In this paper, heat transfer characteristics of natural convection in an enclosure are investigated by considering variable thermal properties. The heated enclosure with an aspect ratio of unity is full of an alumina-water nanofluid. To analyze the effect of different thermal properties on the flow and temperature distributions, many comparisons are conducted for various cases at various Rayleigh numbers and volume fractions of nanoparticles (1–9.5%). The effect of low-gravity conditions on natural convection is investigated by using the gravity values of 0.25 g (2.45 m/s 2 ), 0.5 g (4.9 m/s 2 ), 0.75 g (7.35 m/s 2 ) and 1.0 g (0.98 m/s 2 ). It was found that larger temperature gradients near the heated and cold walls can be obtained by increasing the Rayleigh number. By increasing the value of gravity, the flow velocity increased along the y direction. This indicated that gravity has great influence on enhancement of heat transfer. The investigation of the volume fraction of nanoparticles shows that the variation of the Nusselt number for high volume fraction presented a more flat profile than for low volume fraction. The Nusselt number decreased with an increase of the volume fraction. Results for cases with connected and unconnected heated walls are presented. The results showed that heat transfer for the case with the nanoparticle volume fraction of 1% at 1.0 g increased by 89.9% using an unconnected heated wall compared to the connected heated wall.